Dual embeddedness? Innovation capabilities, multinational subsidiaries, and solar power development in South Africa. (August 2021) - Davy, Elder; Hansen, Ulrich E.; Nygaard, Ivan
Abstract: One longstanding strand of research in the development studies literature has concerned itself with the development of innovation capabilities in developing-country firms. As most of this literature focuses on domestic firms, foreign-owned firms, such as subsidiaries of multinational companies (MNC), have received much less attention. In this paper, we address this knowledge gap by conducting an in-depth study exploring the learning and capability-building trajectory of a single MNC subsidiary operating in the market for solar power in South Africa. We employ a conceptual framework enabling us to explore capability building arising from the dual embeddedness of the subsidiary respectively in the corporate network of the parent company and the host economy in South Africa. We find that the subsidiary managed to achieve an advanced level of innovation capabilities in a short period. Initially, learning through interaction with the parent company and firm-internal learning in the subsidiary were found to have been essential in the early stage of the capability building process. Learning through collaboration with local research institutes became important only after a certain level of capabilities had already been acquired. Learning by hiring was important throughout, but it became gradually more important in parallel with the increasing specialisation of the local workforce in solar power projects. Our findings are particularly relevant for a new type of 'born global' MNCs that is becoming dominant in the global market for renewable energy. Finally, we point to the importance of regulatory conditions in shaping the degree of knowledge transfer and capability building of MNC subsidiaries.